Transaction cost theory refined: Theoretical and empirical evidence from a business-to-business marketing perspective - Markus Ungruhe; Henning Kreis; Michael Kleinaltenkamp (Freie Universität Berlin, Fachbereich Wirtschaftswissenschaft, 2010)
Recently, integrating Transaction Cost Economic (TCE) and Resource Based View (RBV) arguments has become one of the most prominent theoretical approaches in research on business relationships. We question this dominance and strengthen an exclusive TCE perspective by recalling two of the core TCE constructs in order to achieve full exploitation of TCE reasoning. We discuss the transaction attributes 'asset specificity' and 'uncertainty' and identify conceptual gaps that lead to ambiguous results regarding the test of TCE guided hypotheses in prior relationship marketing and management research. To overcome these problems, we redefine both concepts and show that they are interconnected in more complex ways than past empirical research has accounted for. Hypotheses are derived and tested empirically in a cross-sectional online-survey setting by using means of structural equation modelling.
Keywords: 330; new institutional economics; risk; uncertainty; asset specificity; Lieferanten-Kunden-Beziehung; Transaktionskosten; Theorie; Schätzung; Deutschland